Exploring the Impacts of Built Environment on Commute Mode Choice: Evidence from China. (6th July 2022) - Xianyu, Jianchuan
Abstract : Car dependency and its negative consequences have created the urgent need for a better understanding of the determinants of car ownership and use. To get people out of their cars, great importance has been attached to the connection between the built environment and travel behaviour. However, the mediating effect of car ownership is ignored in most studies of the relationship between the built environment and travel mode. The aim of this paper is to contribute to our understanding of the influence of the built environment on commute mode choice by considering the intermediary nature of car ownership based on a nationally representative sample from China. A recursive simultaneous bivariate probit model, which allows the analysis of the mediating effect of car ownership while modelling the relationship between the built environment and commute mode choice behaviour, is employed. Results indicate that the built environment attributes at the neighbourhood level do have both direct and indirect effects on commute mode choice. For most environmental attributes, their effects on commute mode choice are greater than their effects on car ownership. Residents may be less dependent on the car if their neighbourhoods are well-designed with more balanced land use and more attractive local job opportunities are available. The research findings suggest that land use policy should be given enough consideration in strategies for car use reduction, while more case studies are needed to examine whether results from this study can be extended to other cities.